The extracontractual civil liability of children and adolescents - Córdova López, Ocner (2020)
When children and adolescents act with discernment, they are civilly responsible for the damages they may cause; however, when the harm is caused by a child who does not have the ability to discern, no responsibility can be attributed to him, since he has not had the ability to understand or love the act that has caused harm. However, the victim can not be without compensation for the unjust damage suffered, it is very likely that children and adolescents do not have a heritage that they can count on for compensation; In this case, in order that the victim is not unfairly affected, some civil codes have provided that in these cases the parents or legal representatives of the minor must respond. Our Civil Code, although in its article 458 ° has regulatedthe civil responsibility of the minor capable of discernment, however, after the repeal of articles 1975 ° and 1976 ° omits to regulate regarding the civil responsibility of parents for the facts harmful of their minor children.